Cracking behaviour of coal ash concrete based on acoustic emission technique - Abdul Muiz, Hasim (2023)
The continual rise of the power sector has resulted in massive production of coal waste by-products known as coal bottom ash (CBA) and fly ash (FA), which are formed when raw coal is burned to generate electricity. The disposal of CBA and FA contributes significantly to major environmental hazards and thereby extensive efforts are required to utilize these wastes. Recently, CBA in concrete has been successfully investigated in terms of microstructure, durability, and other common properties. However, it is non-trivial to remark that a topic that received less exploration is serviceability of structural performance, and the main concern being whether CBA aggregate affects the cracking of structural concrete due to the cyclic load. The crack identification is critically important because it gives the first sign of serious trouble indicating the load-carrying capacity and deficiencies in strength of structural elements. Therefore, this research aims to investigate the mechanical properties of plain concrete and cracking behaviour of reinforced concrete (RC) beam with inclusion of CBA. Thus, specimens were designed into four distinct combination replacements between half (50%) and full (100%) of coarse aggregate and fine aggregate using CBA with addition of 20% FA to the cement amount. The fresh concrete was tested by workability test while plain concrete specimens were made for compressive test, splitting tensile test and flexural tests to investigate the mechanical properties of concrete. Then RC beam specimens were cast for a 4-point bending test subjected to a cyclic load method to evaluate cracking behaviour. The assessment of the RC beam also used the acoustic emission (AE) technique that worked purposely for non-destructive testing (NDT). The experimental result shows that compressive strength of concrete for all replacements achieves targeted strength of 30 MPa at 28 days. However, splitting tensile and flexural strength decreased slightly when increasing the volume of CBA in the design mixture. Furthermore, the cyclic load criteria with respect to deviation from linearity (DFL) is promising to correlate to RC beam failure according to deflection in each specific load cycle. Nonetheless, the cracking behaviour of RC beams was mainly influenced by porous and high crushing index of coarse CBA and all tested RC beams failed to the flexural and shear crack failure. In AE parameter-based analysis, the correlation between average frequency and RA (rise time/amplitude) value shows that nucleation of cracks in early cycles are always recorded as a tensile mode with a high average frequency. Then, the crack switches to shear mode containing a high RA value at a subsequent cycle until ultimate load. The AE findings are well matched and consistent with the real visual inspection of crack damage that appeared on the RC beam surface during the experimental work in a laboratory. Thus, the obtained finding in this study indicates that the crack identification from AE technique is effective for structural monitoring, so it could benefit understanding the properties of CBA on the performance of concrete structures. Finally, the excessive usage of CBA in concrete contribute to large numbers of crack while producing wide crack width, but the utilization of CBA as a 50% gravel replacement has good structural performance under cyclic load test as they are comparable to the control RC beam.